2006
DOI: 10.2307/30032442
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Health-Care Workers to HIV / AIDS

Abstract: The current 5% prevalence rate of HIV in Nigeria represents a significant population of people living with HIV/AIDS (PLWHA). Discrimination against PLWHA has profound impact on the care and support required for their optimal management particularly in resource-constrained settings. The study sought to assess the knowledge of health-care providers about HIV/AIDS, determine the potential for discrimination in the provision of services based on patients' HIV sero-status and review the factors that may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
33
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 0 publications
9
33
1
1
Order By: Relevance
“…22,47,68,80,81 Possessing basic and health care sector specific knowledge about HIV and having an understanding of PLWH's rights can contribute to more positive interactions between PLWH and health care providers and better quality care, 38,58 but information provision alone is insufficient as knowledge does not automatically change attitudes. 16,21,37,64,82 It does, however, form the basis upon which informed attitudes are developed and is, therefore, central to positive changes in attitudes and behaviour. 16,77 Consequently, we consider the provision of information to be an important first but certainly not final step in creating and maintaining positive experiences for PLWH in health care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,47,68,80,81 Possessing basic and health care sector specific knowledge about HIV and having an understanding of PLWH's rights can contribute to more positive interactions between PLWH and health care providers and better quality care, 38,58 but information provision alone is insufficient as knowledge does not automatically change attitudes. 16,21,37,64,82 It does, however, form the basis upon which informed attitudes are developed and is, therefore, central to positive changes in attitudes and behaviour. 16,77 Consequently, we consider the provision of information to be an important first but certainly not final step in creating and maintaining positive experiences for PLWH in health care.…”
Section: Discussionmentioning
confidence: 99%
“…21,33,68,91,93,94 Interventionists may consider incorporating opportunities for self-reflection on stigmatized behaviors frequently associated with HIV such as homosexuality, commercial sex work, and drug use as addressing layered stigmas, if present, may yield even greater changes in negative attitudes. 16,[95][96][97][98] Before interpersonal level interventions geared to PLWH and health care providers can be implemented, it is imperative that supportive structural conditions for the equal treatment of PLWH in the health care settings are in place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV/AIDSrelated discrimination occurs everywhere, but PLWHA may have more serious consequences in healthcare settings (Ahsan Ullah 2011). According to previous findings, HIV/ AIDS-related discrimination has been extensively documented among healthcare providers, and an average level of discriminatory attitudes exists among health care workers in many studies (Sadob et al 2006;Hossain and Kippax 2010).…”
Section: Discussionmentioning
confidence: 90%
“…These can include the perception that they are not at risk of the disease for those who do not know their HIV status. And for PLHA, they can include internalized stigma, lowered self-esteem, depression, and changes in behavior (e.g; not using the available services) because of the fear of stigma (8,9). It was indicated that higher perceived HIV stigma scores amongs clients with HIV were significantly and negatively correlated with the quality of life (10).…”
Section: Introductionmentioning
confidence: 97%